Gastro-Retentive Floating Drug Delivery System: A Comprehensive Review - Malpani P. Shraddha,; Dr. Nishan N. Bobade,; Dr. Shrikant D. Pande,; Dr. Sandeep C. Atram,; Dr.Vikrant P. Wankhade, (Asian Journal of Pharmaceutical Research and Development, 2026)
Floating Drug Delivery Systems are an advanced gastroretentive approach designed to improve the bioavailability and therapeutic efficacy of drugs that have a narrow absorption window or are unstable in the intestinal environment. These systems remain buoyant in gastric fluids due to their low density or gas-generating mechanisms, allowing prolonged gastric retention and controlled drug release at the desired site. FDDS are broadly categorized into effervescent and non-effervescent systems, including bilayer tablets, raft-forming systems, and colloidal gel barrier formulations. Various formulation and physiological factors such as polymer type, tablet size, gastric motility, and fed or fasted state significantly influence the gastric retention time and drug release behavior. Among the preparation techniques, direct compression, wet granulation, and effervescent methods are widely employed. FDDS offer distinct advantages like enhanced bioavailability, reduced dosing frequency, and improved patient compliance, though they are unsuitable for drugs unstable in acidic media.